(untitled) (Baghdad Science Journal, 2025)
A simple , sensitive and accurate spectrophotometric method for the trace determination of bismuth (III) has been developed .This method is based on the reaction of bismuth (III) with arsenazo(III) in acid solution (pH=1.9) to form a blue water soluble complex which exhibits maximum absorption at 612nm .Beer’s law is obeyed over the concentration range of 2-85 ?g bismuth (III) in a final volume of 20 mL( i.e. 0.1 – 4.25?g.mL-1) with a correlation coefficient of (0.9981) and molar absorptivity 1.9×104 L.mol-1.cm-1 . The limit of detection (LOD) and the limit of quantification (LOQ) are 0.0633 and 0.0847 ?g.mL-1 , respectively . Under optimum conditions,the stoichiometry of the reaction between bismuth (III) and arsenazo(III) reagent was found to be 1:2. The recoveries were obtained in the range of 98.9 - 100.0% and a relative standard deviation of ±0.59 to ±2.73% depending on the concentration level of bismuth. The effect of interferences by a number of common cations and anions in the presence of composite mixture has been studied .The proposed method has been applied successfully for determination of bismuth in water samples and veterinary preparation .